4
$\begingroup$

The value of the logarithmic expression $\log_x \dfrac{x}{y} +\log_y \dfrac{y}{x},\text{where}\quad x\geq y>1\quad$ can never be

$\bf\text{options}$ a.) $-1\quad$ b.)$\quad0.5\quad$ c.) $\quad0\quad$ d.) $\quad1$

$$\begin{align}\log_x \dfrac{x}{y} +\log_y \dfrac{y}{x}&=1-\log_x y +1-\log_y x\\ &=\frac{2\log_x y}{\log_x y}-\frac{(\log_x y)^2}{\log_x y} -\frac{1}{\log_x y}\\ &=-\frac{ (\log _{x}y-1)^{2} }{ \log _{x}y}\end{align}$$

here if i input $x=y=2$ then option $0$ is removed , not sure how to deduce the rest.

Wolfram does gives the answer as option $1$

$\endgroup$
5
  • $\begingroup$ This clever reduction might be too clever. Think about the range of the function f(x) = x + 1/x. $\endgroup$ Mar 5, 2015 at 21:26
  • $\begingroup$ @JohnBrevik: but range of $f(x)=x+1/x$ is $\geq 2$ or $\leq -2$ but how is that related to the question $\endgroup$
    – R K
    Mar 5, 2015 at 21:32
  • $\begingroup$ Try changing the base of the the $\log_y x$ into a logarithm with base $x$.That should answer how this is related to question. $\endgroup$
    – kingW3
    Mar 5, 2015 at 22:31
  • 6
    $\begingroup$ $$\begin{array}{l}\text{The logarithmic expression can never be strained.}\cr \text{It droppeth as the gentle rain from heaven}\cr \text{Upon the place beneath. It is twice blessed:}\cr \text{It blesseth him that gives and him that takes.}\end{array}$$ $\endgroup$
    – Will Jagy
    Mar 5, 2015 at 23:19
  • $\begingroup$ @RK $\log_xy = \dfrac{1}{\log_yx}$. This should help you understand how the solution is related to John's comment. $\endgroup$
    – lakshayg
    May 1, 2015 at 12:27

5 Answers 5

6
$\begingroup$

In light of @John's leading comment, if we put $$A=\log_x \dfrac{x}{y} +\log_y \dfrac{y}{x}$$ then $$A=2-\left(\log_x y +\log_y x\right)=2-(z+\frac{1}{z})\le 0,~~~z=\log_x y$$ This means that another option could be chosen. In fact, using maple says that: it can never be $0.5$ also:

 > implicitplot(log[x](x/y)+log[y](y/x) = 1/2, x = 1 .. 100, y = 1 .. 100);

enter image description here

$\endgroup$
3
  • $\begingroup$ Wolfram also says that , m confused. $\endgroup$
    – R K
    Mar 6, 2015 at 15:06
  • $\begingroup$ I'm confused as to the confusion. You're subtracting a number at least as big as 2 from 2. It better not be 0.5 :) $\endgroup$ Mar 6, 2015 at 16:20
  • $\begingroup$ @JohnBrevik: Indeed, your comment solved the problem and gave the OP what he wanted to know. It seems that it shoudn't be 0.5. $\endgroup$
    – Mikasa
    Mar 6, 2015 at 17:59
4
+50
$\begingroup$

$$\begin{align}\log_x \dfrac{x}{y} +\log_y \dfrac{y}{x}&=1-\log_x y +1-\log_y x\\ &=2-\dfrac{\ln y}{\ln x} -\dfrac{\ln x}{\ln y}\\ &=2-\dfrac{\ln² y+\ln²x}{\ln x \ln y} \\ &=-\dfrac{(\ln y-\ln x)²}{\ln x \ln y}\end{align}$$

this value does never equal ${1,0.5}$

$\endgroup$
2
  • $\begingroup$ But how did u deduced that $\dfrac{(\ln y-\ln x)²}{\ln x \ln y}$ can't be $1,0.5$. $\endgroup$
    – R K
    Apr 26, 2015 at 0:53
  • $\begingroup$ @RK it is a negative value $=-\dfrac{(\ln y-\ln x)²}{\ln x \ln y}$ $\endgroup$
    – Abr001am
    Apr 26, 2015 at 9:13
2
$\begingroup$

Note: We start in the same way as OP did and then we proceed accordingly.

We consider

\begin{align*} \log_x\frac{x}{y}+\log_y\frac{y}{x}\qquad\qquad\qquad x\geq y>1\tag{1} \end{align*}

  • Validity of domain: At first, we check the domain and observe that since $\log_bz$ is defined for any $z>0$ and for $b>0, b\ne 1$ the expression (1) is valid for all $x\geq y>1$.

  • Since $\log_bx=\frac{\log_kx}{\log_kb}$ for any bases $b,k>1$ we obtain \begin{align*} \log_xy=\frac{\log_yy}{\log_yx}=\frac{1}{\log_yx}\tag{2} \end{align*}

  • We also keep in mind that for $x\geq y > 1$ \begin{align*} 0<\log_xy\leq 1 \tag{3} \end{align*}

Options b.) and d.)

We start now similarly as OP did: \begin{align*} \log_x&\frac{x}{y}+\log_y\frac{y}{x}\\ &=\log_xx-\log_xy+\log_yy-\log_yx\\ &=2-\log_xy-\frac{1}{\log_xy}\\ &=-\frac{1}{\log_xy}\left((\log_xy)^2-2\log_xy+1\right)\\ &=-\frac{\left(\log_xy-1\right)^2}{\log_xy}\leq 0\tag{4} \end{align*}

In (4) we use $0<\log_xy\leq 1$ accordingly to (3).

Conclusion: The expression (1) is less or equal to zero whenever $x\geq y >1$. Therefore it can never be option b.) with value $0.5$ or option d.) with value $1$

Options a.) and c.)

We now set $z=\log_xy$ and consider accordingly to (4) the expression

\begin{align*} -\frac{\left(z-1\right)^2}{z}=a\qquad\qquad a \in \mathbb{R} \end{align*} or equivalently \begin{align*} z^2-(a-2)z+1=0 \end{align*} with solutions \begin{align*} z_{1,2}=1-\frac{a}{2}\pm\frac{1}{2}\sqrt{a(a-4)} \end{align*} Now, if we set accordingly to option c.) $a=0$ we see $z_{1,2}=1$ and therefore $$\log_xy=1 \Rightarrow x=y$$

Conclusion: Letting $x=y>1$, we get

\begin{align*} \log_x&\frac{x}{y}+\log_y\frac{y}{x}\\ &=\log_x\frac{x}{x}+\log_x\frac{x}{x}\\ &=2\log 1\\ &=0 \end{align*} and so we can't skip option c.)


Next we set $a=-1$ and get $z_{1,2}=\frac{1}{2}(3\pm \sqrt{5})$

Conclusion: Since $z_2=\frac{1}{2}(3-\sqrt{5})< 1$ we see that according to (3) we also find a solution for option a.) with value $-1$

$\endgroup$
2
$\begingroup$

\begin{align}\log_x \dfrac{x}{y} +\log_y \dfrac{y}{x}&=1-\log_x y +1-\log_y x\end{align}

Let $y^p = x$, therefore $\log_y x =p$ and $ \log_x y = \frac1p $ $\qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad$ So, $1-\log_x y +1-\log_y x = 2 - (p + \frac1p)$

For the RHS of above expression to equate to -1, 0.5, 0, 1, we must have p + $\frac1p$ = 3, 1.5, 2, 1 respectively. So, we have to solve for $p$ the corresponding quadratic equations which work out to be $\quad$ $p^2-3p+1=0$, $\quad$ $2p^2-3p+2=0$, $\quad$ $p^2-2p+1=0$, $\quad$ $p^2-p+1=0$. $\quad$$\quad$$\quad$$\quad$$\quad$$\quad$$\quad$$\quad$$\quad$$\quad$$\quad$$\quad$$\quad$$\quad$$\quad$$\quad$$\quad$$\quad$$\quad$$\quad$$\quad$$\quad$$\quad$$\quad$$\quad$$\quad$$\quad$$\quad$$\quad$$\quad$$\quad$$\quad$$\quad$$\quad$$\quad$$\quad$$\quad$$\quad$$\quad$$\quad$$\quad$$\quad$ On solution we obtain $p=(3+\sqrt{5})/2 $ & $p=(3-\sqrt{5})/2$ for the first, $\quad$$\quad$ $p=1$ & $p=\frac12$ for the second, $\quad$$\quad$ $p=1$ for the third, $\quad$$\quad$ and $p=(1+\sqrt3i)/2$ & $p=(1-\sqrt3i)/2$ for the fourth.

Since $y^p = x$, imaginary $y$ would be out of domain of the problem and also make $x$ outside the domain of the problem (domain is x,y > 1, i.e. x, y real) and hence solution $p=1$ which corresponds to $\log_x \dfrac{x}{y} +\log_y \dfrac{y}{x}=1$ is not possible. So, answer is option d.) $\quad$$\quad$$\quad$$\quad$$\quad$$\quad$$\quad$ Also notice that for second equation, $p=1$ is a false root, and $p=\frac12$ would make $y \gt x$ which is also outside the domain of the problem. So, this equation which corresponds to $\log_x \dfrac{x}{y} +\log_y \dfrac{y}{x}=\frac12$ is also not possible

$\endgroup$
1
$\begingroup$

In this question, take $log_y x=a$. Then the expression$(E)$ given in the question reduces to $$E=2-(a+\frac 1a)$$ Now $a$ and $\frac1a$ are both positive or both negative. Since $x,y>1$ $a$ is positive. Using $A.M-G.M$ inequality you can say that $$a+\frac 1a \ge 2\sqrt{a.\frac 1a}\ge 2.$$Hence $$E=2-(a+\frac 1a)\le 2-2\le 0$$ Hence options $(b)$ and $(d)$ are ruled out. For $E=0$, equality must hold in the inequality, i.e., $a=1$. This is possible when $x=y$. For $(a)$ to be true $$a+\frac 1a=3\implies a^2-3a+1=0\implies a=\frac {3\pm\sqrt5}2$$But $x>y\implies a>1$. Therefore $a=\frac {3+\sqrt5}2$. This is very well possible. Hence ($a$) and ($c$) are correct.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.